Tree Mortality in Gap Models: Application to Climate Change - Keane, Robert E.; Austin, Mike; Field, Christopher; Huth, Andreas; Lexer, Manfred J.; Peters, Debra; Solomon, Allen; Wyckoff, Peter (Climatic change, 2001)
Gap models are perhaps the most widely used class of individual-based tree models used in ecology and climate change research. However, most gap model emphasize, in terms of process detail, computer code, and validation effort, tree growth with little attention to thesimulation of plant death or mortality.